Realización de un cortometraje animado para sensibilizar acerca del cuidado de los adultos mayores y la posesión de mascotas en los asilos de Quito - Villacreces Hinnaoui, Juan José (2020)
This research addresses the loneliness experienced by older adults in Ecuador, especially for those who live in nursing homes and spend their days alone, and the importance of companionship for their health and well-being. The objective of this research is to make an animated short film that portrays this problem and the social reality experienced by older adults living in nursing homes in Quito, in order to raise awareness about how difficult it is for older adults to separate themselves from their loved ones and their pets. To capture the essence of this problem and to show how important companionship is for older adults, serval characters and scenarios were created in 3D as part of the short animated film. The target audience for this research are the families of older adults as well as the care centers, asylums or residences, regardless of their socio-economic level, their internet availability or if they have the necessary means to see the short animated film. The project has a qualitative nature since it describes, informs and interprets all the content taken from secondary sources about the situation experienced by older adults and the benefits of companionship from their relatives and pets. The contextualization of 3D characters in the animated short film was based on interviews conducted with older adults. In addition, personal creativity was added to adapt this problematic experienced by older adults due to the lack of companionship into a short animated film and create a story that demonstrates their reality. In conclusion, the research portrays the importance of companionship needed for their well-being and quality of life of older adults, which is reflected in the animated short film.